2015
DOI: 10.1097/scs.0000000000001306
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Cell Therapy Improves Bone Healing

Abstract: The combination of a PC-mobilizing and traffic-enhancing agent improved bony regeneration of calvarial defects in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…In the present in vivo study using a rat tibial model, it was examined whether substances that enhance the recruitment of progenitor cells could be used as an approach to promote osseointegration of bone‐anchoring implants. Plerixafor is known to act as a CXCR4 antagonist, and hence mediate progenitor cell mobilization . Therapeutic treatments with plerixafor rely on the ability of the drug to mobilize stem cells and increase their availability.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the present in vivo study using a rat tibial model, it was examined whether substances that enhance the recruitment of progenitor cells could be used as an approach to promote osseointegration of bone‐anchoring implants. Plerixafor is known to act as a CXCR4 antagonist, and hence mediate progenitor cell mobilization . Therapeutic treatments with plerixafor rely on the ability of the drug to mobilize stem cells and increase their availability.…”
Section: Discussionmentioning
confidence: 99%
“…Plerixafor is known to act as a CXCR4 antagonist, and hence mediate progenitor cell mobilization. [7][8][9]18 Therapeutic treatments with plerixafor rely on the ability of the drug to mobilize stem cells and increase their availability. SDF-1 is known as a chemokine that recruit stem cells to the site of healing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that both VEGF and BMPs increase the differentiation of pre-osteoblasts and that they elicit a synergistic effect on bone formation. 13 18 …”
Section: Introductionmentioning
confidence: 99%